Aneurysmal Bone Cyst of the Calcaneus - Kaplanoğlu, Veysel (J Clin Imaging Sci, 2014)
Aneurysmal bone cysts (ABCs) are benign, non-neoplastic, expansile, vascular, locally destructive lesions. The lesion may arise de novo (65%) or secondarily (35%) in pre-existing benign or malignant lesions (giant cell tumor, osteoblastoma, chondroblastoma, angioma, and others). The calcaneus is a rare localization for ABC, comprising only 1.6% of the cases. In this paper, we present a case of a female patient with a 3-month history of heel pain that got worse and was accompanied by swelling and difficulty in walking. The magnetic resonance images of the postero-lateral calcaneus showed a contrast-enhanced cystic lesion located in the medullary cavity; exophytic portion of the tumor extended into the soft tissue causing distinctive cortical thinning. Heterogeneous hyperintense septae formations and blood level components were also detected. After correlation with pathology results, the lesion was diagnosed as an ABC. Since an ABC of the calcaneus is a rarely seen phenomenon, we present the radiologic findings in this case and a review of the literature.